ANALYSIS OF FACTORS INFLUENCING PATIENT SATISFACTION LEVELS IN IMPROVING SERVICE QUALITY IN EMERGENCY ROOMS: A SYSTEMATIC LITERATURE REVIEW - Septiari Candra Puspitasari; Masruroh; Ade Armada Sutedja (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Patient satisfaction is an important indicator of healthcare service quality, particularly in Emergency Departments (EDs), where rapid and accurate care is essential. Various factors have been reported to influence patient satisfaction, but the findings remain inconsistent across studies. Objective: This study aimed to identify and analyze the factors influencing patient satisfaction in improving the quality of ED services. Design: A Systematic Literature Review was conducted following the PRISMA 2020 guidelines. Data Sources: Literature was searched in PubMed, ScienceDirect, ProQuest, and Google Scholar from January to February 2025. Articles published between 2013 and 2024 were identified using keywords related to patient satisfaction, service quality, and emergency department services. Review Methods: Original research articles in English or Indonesian and available in full text were included. The selection process involved identification, screening, eligibility assessment, and inclusion stages. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, and data were synthesized narratively. Results: Of 3,636 identified records, 7 studies met the inclusion criteria. Patient satisfaction was influenced by healthcare provider service quality, communication and information delivery, responsiveness and waiting time, physical facilities and environmental cleanliness, pharmacy services, and supporting healthcare services. Communication and empathy were the most consistently reported factors, while physical facilities (tangibles) showed the strongest influence on patients’ perceptions of service quality. Conclusion: Patient satisfaction in EDs is influenced by clinical, communication, organizational, and environmental factors. Improving communication skills, reducing waiting times, optimizing digital-based service systems, and enhancing facility cleanliness and comfort are recommended to improve the quality of emergency care services.